Bivalent interaction of the PZP domain of BRPF1 with the nucleosome impacts chromatin dynamics and acetylation - Klein, Brianna J.; Muthurajan, Uma M.; Lalonde, Marie-Eve; Gibson, Matthew D.; Andrews, Forest H.; Hepler, Maggie; Machida, Shinichi; Yan, Kezhi; Kurumizaka, Hitoshi; Poirier, Michael G.; Côté, Jacques; Luger, Karolin; et al. (Nucleic acids research, 2016)
BRPF1 (bromodomain PHD finger 1) is a core subunit of the MOZ histone acetyltransferase (HAT) complex, critical for normal developmental programs and implicated in acute leukemias. BRPF1 contains a unique assembly of zinc fingers, termed a PZP domain, the physiological role of which remains unclear. Here, we elucidate the structure-function relationship of this novel epigenetic reader and detail the biological and mechanistic consequences of its interaction with nucleosomes. PZP has a globular architecture and forms a 2:1 stoichiometry complex with the nucleosome, bivalently interacting with histone H3 and DNA. This binding impacts the nucleosome dynamics, shifting the DNA unwrapping/rewrapping equilibrium toward the unwrapped state and increasing DNA accessibility. We demonstrate that the DNA-binding function of the BRPF1 PZP domain is required for the MOZ-BRPF1-ING5-hEaf6 HAT complex to be recruited to chromatin and to acetylate nucleosomal histones. Our findings reveal a novel link between chromatin dynamics and MOZ-mediated acetylation.